The party for 1925. (1925)
1 photograph : sepia toned 8 x 14 cm Walter Stanley Monroe, Samuel J. Foote, Samuel F. Milley, Donnelly and William Robertson Warren standing in front of the Grand River, Codroy Valley. Title from album caption. Walter Stanley Monroe (1871-1952) was born in Dublin, Ireland, son of John and Elizabeth (Moule) Monroe. Married Helen Smith. In 1923 Monroe entered politics and ran unsuccessfully against William Coaker in Bonavista. William Warren appointed Monroe Minister in his second administration formed in 1924. Monroe was appointed to the Legisaltive Council in 1933. Samuel J. Foote (1873-1936) was born in Grand Bank in 1873. Foote was called to the Newfoundland Bar in 1899 and went to practice with Sir James Winter. Foote entered into politics in 1904. Foote died on December 8, 1936. Samuel F. Milley (1867-1939) was born in St. John's in 1867. Milley was a prominent dry goods merchant in St. John's from 1890's and was a member of the Legisaltive Council for more than 30 years. Milley died in Montreal on February 12, 1939. William Robertson Warren (1879-1927), son of William Henry and Jessie (Harvey) Warren, was born in St. John's in 1879. He began his political career in 1903, and became Prime Minister of Newfoundland from July 1923 - April 1924. Warren died suddenly on December 31, 1927. Good An album containing 323 black and white photographs and 25 pages of text, covering the years 1914 to 1937 of the FOMOWA Fishing Club on the Grand Codroy River on the west coast of Newfoundland. The album's images have been digitized as separate items.